DIGITAL MEDIA AND THE ALGERIAN FAMILY: FROM INFLUENCE TO RESHAPING. A CONCEPTUAL APPROACH - Ben Dar Nessima; Boussahla Ines (International Journal of Innovative Technologies in Social Science, 2025)
Today’s world is experiencing changes that are almost revolutionizing the concepts and lifestyle of previous years. These changes are leading the media and communication to form a new mind that is cognitively, emotionally, and behaviorally different from previous generations. Indeed, today’s human being is almost facing the media sweep. From here stems the problem of studying the negative role it plays. The media system in the context of performing its roles and interacting with society, through which the incoherent set of social values is strengthened It is contradictory in its trends due to the diversity of its sources and the differences in the intellectual and cultural foundations built on it, which finds clear effects in the recipients’ attraction towards it, and works to meet the unstable psychological and social needs and cultural and civilizational peculiarities that society has settled on for hundreds of years. The media is considered an essential partner in the process of change because of what it entails. It has a high ability to achieve the process of communication very quickly between the components of one society on the one hand, and between multiple societies on the other hand This is because the process of change that results in manifestations of urbanization or manifestations of backwardness depends on the degree of interaction with others, on the level of the communication and communication process, on the nature of this process, the forms and tools used in it, and the goals that lie behind it. Based on the above, the study seeks to monitor the role of media and communication in relation to the family and its effects in shaping new values and trends, formulating new values, or abolishing stable values that are not compatible with the cultural and civilizational specificities on which Algerian society has settled for some time by answering a set of questions. Among the most prominent: • What are the functions and roles of media and communication in the digital age? • Have media and communication in the digital age influenced the shaping of Algerian family values? • Do media and communication play a role in building new family values, undermining established values, or reproducing old values in a new way? • How are family values shaped by the diverse content disseminated by these media?